2019
DOI: 10.7150/jca.31697
|View full text |Cite
|
Sign up to set email alerts
|

AIB1 predicts tumor response to definitive chemoradiotherapy and prognosis in cervical squamous cell carcinoma

Abstract: Amplified in breast cancer 1 (AIB1) gene, has been reported to be associated with biological malignancy in several cancers. However, the molecular status of the AIB1 gene in cervical cancer and the clinicopathological/prognostic significance of AIB1 expression in chemoradiotherapy (CRT) sensitivity have not been determined. In our present study, we found that the high expression of AIB1 was frequent detected in specimens of cervical cancer patients, and this was significantly correlated with CRT response (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, ER signaling is associated with HPV infection and cervical cancer in many aspects, including pro-carcinogenic and anti-carcinogenic relationship [ 127 ]. Recent study found that SRC-3 was more frequently high expressed in cervical cancer (52.7%) compared to normal cervical tissues (30%), and high level of SRC-3 is significantly associated with aggressiveness and chemoradiotherapy resistance [ 47 ]. It suggests that SRC-3 may be considered as a potential target and predictor for the treatment of this disease.…”
Section: Implication Of Src-3 In Cancermentioning
confidence: 99%
“…However, ER signaling is associated with HPV infection and cervical cancer in many aspects, including pro-carcinogenic and anti-carcinogenic relationship [ 127 ]. Recent study found that SRC-3 was more frequently high expressed in cervical cancer (52.7%) compared to normal cervical tissues (30%), and high level of SRC-3 is significantly associated with aggressiveness and chemoradiotherapy resistance [ 47 ]. It suggests that SRC-3 may be considered as a potential target and predictor for the treatment of this disease.…”
Section: Implication Of Src-3 In Cancermentioning
confidence: 99%
“…The most common pathological type of cervical cancer is cervical squamous cell carcinoma (CESC). [1] When patients with CESC are diagnosed and treated in the early stage of the tumor, the chance of survival can be increased and may push the 5-year survival rate to 90%. [2] However, the early symptoms of cervical cancer are not obvious.…”
Section: Introductionmentioning
confidence: 99%
“…76 Recent studies from Riegel's laboratory and others indicated a role of AIB1 isoform in the invasion and progression of breast cancer. 74,[77][78][79][80][81][82] While AIB1 plays a clear role in nuclear receptor biology, it has also been implicated in chromatin remodeling. AIB1 was isolated as the p300/CBP cointegrator-associated protein (p/CIP) based on its ability to interact with the C terminus of CBP and has been shown to bind to p300 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Like AIB1, E6AP has been shown to have a role in steroid receptor coactivation and may work in concert with AIB1 for this function 76 . Recent studies from Riegel's laboratory and others indicated a role of AIB1 isoform in the invasion and progression of breast cancer 74,77–82 …”
Section: Introductionmentioning
confidence: 99%